1999
DOI: 10.1080/03014223.1999.9518195
|View full text |Cite
|
Sign up to set email alerts
|

Dominant and subordinate behaviour of captive brushtail possums (Trichosurus vulpecula)

Abstract: Brushtail possums are generally solitary animals. They use a range of olfactory, auditory, visual, and tactile behaviour to achieve spacing between individuals and to establish dominance hierarchies. Existing descriptions of possum behaviour are either not widely available or incomplete, and the function of dominance hierarchies is unclear. Data presented here were collected incidentally during observations of captive possums to determine the effects on dominance status of suppression of reproduction for biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Specifically, phalangerid acoustic behaviours are complex and vary substantially between families and genera, with some species having numerous calls used in various contexts, while other species limited to one known sound (Winter 1976;Kerle 2001). The sounds and observations of associated behavioural displays exhibited by A. ursinus may perform a similar function to those used by other phalangerid species, acting as a defensive threat display in response to potential predators (see Winter 1976;Biggins & Overstreet 1978;Spurr & Jolly 1999;Hogan & Morrow 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, phalangerid acoustic behaviours are complex and vary substantially between families and genera, with some species having numerous calls used in various contexts, while other species limited to one known sound (Winter 1976;Kerle 2001). The sounds and observations of associated behavioural displays exhibited by A. ursinus may perform a similar function to those used by other phalangerid species, acting as a defensive threat display in response to potential predators (see Winter 1976;Biggins & Overstreet 1978;Spurr & Jolly 1999;Hogan & Morrow 2015).…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, Allen (1982) found that introducing captive possums to swabs of paracloacal gland secretions did not elicit much interest apart from casual sniffing. This lack of response may be related to their captivity, since others have found that scent marking did not elicit responses in penned possums (Kean 1967;Spurr & Jolly 1999).…”
Section: Behavioural Correlatesmentioning
confidence: 94%
“…Possums also have apocrine and Scent glands of the common brushtail possum 199 sebaceous glands associated with large hairs on the pinna and upper lip (Green 1963), and their secretions may be spread by the same behaviour. Saliva and other secretions may be deposited on substrates by gnawing, licking, lip-rubbing, chinning and labial sliding (Biggins 1984;Spurr & Jolly 1999). These scent sources may serve for personal identification (Biggins 1984).…”
Section: Other Scent Sourcesmentioning
confidence: 98%
See 1 more Smart Citation
“…Possums exhibit social behaviours observed in many other mammals, involving social hierarchy, territorial defence, individual recognition and mating [ 17 ]. Dominant males, and occasionally dominant females, exhibit scent marking behaviour including chinning, chesting, cloacal dragging, urine dribbling and face-washing [ 17 , 21 , 22 ]. The purpose of these behaviours has yet to be established, as does the physiological and molecular mechanism behind them.…”
Section: Introductionmentioning
confidence: 99%